Evaluation of B2B pharmaceutical supply chain in Australia - Lin, Chad; Jalleh, Geoffrey (IGI Global, 2015)
© 2015 by IGI Global. All rights reserved. The pharmaceutical industry is one of the most innovative and research-intensive industries in the world. For example, five out of the top global Research and Development (R&D) companies were pharmaceutical companies. However, the industry is lagging behind other industries in adopting Business-to-Business (B2B) and supply chain technologies. With supply chain costs constituting around 25-40% of an organization's operating expenses, it is imperative for senior pharmaceutical executives to minimize this cost. Hence, the main objective of this chapter is to identify key B2B e-commerce management, evaluation, and benefits realization factors and challenges within the Australian pharmaceutical supply chain. The results of this study suggest that pharmaceutical companies not only need to carefully examine their B2B investment management and evaluation practices but also must invest in using appropriate evaluation methodologies for identifying and managing benefits, risks, and costs associated with their investments in B2B and supply chains.